PENDIDIKAN ISLAM DALAM LINGKUNGAN KELUARGA, SEKOLAH DAN MASYARAKAT: Pendidikan Islam, Lingkungan Keluarga, Sekolah, Masyarakat. - jum, jumrianah_jum (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
The Islamic education environment is all conditions and external influences on the progress of education in order to shape individuals and develop the potential of students so that the goals of Islamic education are achieved. This research aims to determine the role of Islamic education in the household environment, school environment and community environment. This research uses the library research method, namely research carried out in a library where the research object is sought through a variety of library information in the form of books, encyclopedias, scientific journals, newspapers, magazines, documents and so on. In carrying out educational development, indirectly between households, schools and the community there has been close cooperation in educational practices. In the household environment, parents lay the foundations of education, especially in terms of personality formation, moral and religious values ??from birth. Then it is continued and developed with various materials in the form of knowledge and skills carried out by the school. Parents of children monitor and assess the results of this school's education in daily life and in the community environment and participate in controlling, distributing and developing and improving it.